The Role of Familiarity in Increasing Repurchase Intentions in Online Shopping - Sudirman Zaid (Journal of Economics, Business, and Accountancy Ventura, 2020)
This study aims to determine the relationship between trust, satisfaction, and repurchase intention at online shopping providers, such as Tokopedia, Bukalapak, Lazada, Zalora, and Blibli, in Kendari City. In detail, this study also aims to determine the role of familiarity in strengthening the relationship between trust, satisfaction, and repurchase intentions. There are 250 respondents involved in this study obtained through convenience sampling technique. The analysis is carried out in 2 stages. The first stage is to simultaneously test the role of trust and satisfaction in increasing repurchase intention. The second stage is to determine the role of familiarity as a moderating variable. Moderating Regression Analysis (MRA) is used to test the causal relationship. The results of this study indicate that familiarity increases the effect of trust on satisfaction, the effect of trust on repurchase intention, and the effect of satisfaction on repurchase intention. The results of this study contribute to the development of the concept of relationship marketing, especially to increase repurchase intention through the development of the concept of familiarity. This study's limitation is that there is no comparison between familiarity attitudes for each online shopping service provider.